Effect of Drip Fertigation on Growth, Yield and Quality of Ridge Gourd[Luffaacutangula(L.)Roxb]. - Rajasree, V.; Pugalendhi, I.; Vasanthi, C.; Shanmugasundaram, T. (University of Jaffna., 2020)
A field experiment was carried out at College Orchard, Department of Vegetable Crops, Horticultural College and Research Institute, Tamil Nadu Agricultural University, Coimbatore to standardize drip fertigation for ridge gourd hybrid COH 1 [Luffa acutangula (L.) Roxb.] The trials were conducted with a view to improve growth, yield and quality to compare the efficacy of water soluble and straight fertilizers for ridge gourd.Afertilizer dosage of 250:100:100 kg NPK ha was -1 adopted for ridge gourd hybrid (COH1). The treatment consisted of seven levels of fertilizers consisting of three levels in straight fertilizers (125,100 and 75 percent of 250:100:100 kgNPKha ) and three levels in water soluble fertilizers (WSF) (125,100 -1 and 75 percent of 250:100:100 kgNPKha ) and a control (100 percent soil application -1 of straight fertilizers) replicated thrice in randomized block design. From the study, it was found that fertigation treatments were significantly superior over the soil application of fertilizers (control). The fertigation treatment with 125 percent WSF (T ) recorded the highest values for growth and physiological characters , vine 5 viz. length (9.65 m), stem girth (5.47 cm) and total chlorophyll content (2.59 mg/100 g). In case of yield parameters, the highest values were registered for fruit length (38.89 cm), fruit girth (19.65 cm), fruit weight (391.11 g), yield per vine (6.05 kg), number of harvests(14.10) and number of fruits/vine (17.84) in 125 percent RDF (250:100:100 kg/ha) through WSF (T ) followed by 100 per cent RDF through WSF. The quality 5 parameters like calcium (15.54 mg/100 g), ascorbic acid (8.14 mg/100g) and phosphorus (0.66 mg/100 g) content were found to be the highest with 125 percent RDF through water soluble fertilizers. Therefore (T ) 125 percent RDF through WSF 5can be recommended for getting increased growth, yield and quality in ridge gourd hybrid COH1.
Keywords: Ridge Gourd.; Drip Fertigation.; WSF.; Growth.; Yield; Quality.